2017
DOI: 10.18632/oncotarget.21003
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin downregulates co-inhibitory receptor expression by targeting Ras-activated mTOR signalling

Abstract: Regulation of T cell function in the steady state is mediated by co-inhibitory receptors or immune checkpoints such as PD-1, CTLA-4, TIM-3 and LAG-3. Persistent antigen stimulation, during chronic viral infections and cancer, results in sustained expression of multiple co-inhibitory receptors and subsequently poor effector T cell function. Immune checkpoint blockade using monoclonal antibodies against PD-1, PDL-1 and CTLA-4 has been implemented as an immunotherapy strategy- resulting in restoration of T cell f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 84 publications
4
27
0
Order By: Relevance
“…Also, we measured the proliferative capacity of CD8 + T cells restricted by different HLA-alleles using CFSE assay according to our previous reports[ 23 , 27 ]. We observed that epitope-specific CD8 + T cells restricted by HLA-B*35Px/B*53 had substantially lower proliferation capacity compared to CD8 + T cells restricted by HLA-B*27/B*57 alleles ( Fig 2F and 2G ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, we measured the proliferative capacity of CD8 + T cells restricted by different HLA-alleles using CFSE assay according to our previous reports[ 23 , 27 ]. We observed that epitope-specific CD8 + T cells restricted by HLA-B*35Px/B*53 had substantially lower proliferation capacity compared to CD8 + T cells restricted by HLA-B*27/B*57 alleles ( Fig 2F and 2G ).…”
Section: Resultsmentioning
confidence: 99%
“…Upon exposure to their cognate epitopes, CD8 + T cells upregulate the expression of co-inhibitory receptors, such as PD-1, TIM-3, and CTLA-4 to self-limit their activation [ 3 , 22 , 23 ]. However, chronic upregulation of co-inhibitory receptors and engagement with their corresponding ligands on antigen-presenting cells (APCs) or Tregs results in the impairment of CTLs functions [ 22 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5F). In parallel we examined whether atorvastatin, due to its immunomodulatory properties as we previously reported 38,49 , can modulate ACE2 expression. However, this was not the case (Extended Data Fig.…”
Section: Cecs Get Infected With Sars-cov-2 and Dexamethasone Reduces mentioning
confidence: 96%
“…This is reflected by a trend in higher expression of inhibitory receptors on CD4 + T cells in C-section delivered cord blood. Inhibitory receptors can be considered as activation markers in an acute setting but in chronic conditions these receptors are associated with T cell exhaustion[ 22 , 23 ]. Furthermore, we analyzed the expression of some genes [TGF-β, NOX2, arginase-2, V-domain Ig suppressor of T cell activation (VISTA) and VEGFα] associated with immunological properties of CD71 + erythroid cells as we have described elsewhere[ 13 , 14 , 16 ].…”
Section: Resultsmentioning
confidence: 99%